Early Career Voices from a Changing Research System - Authors, ECR; Truax, Olivia; Baisden, Troy; Stevens, Craig; Dickson, Benjamin (New Zealand Science Review, 2026)
Aotearoa New Zealand’s research landscape is undergoing a profound transformation. Restructuring across universities, polytechnics, and newly formed Public Research Organisations (PROs) has reshaped not only how research is organised and funded, but also what it feels like to build a career within it. These changes are unfolding amid tightening budgets, growing geopolitical instability, and escalating climate pressures, alongside a broader global crisis of trust in research. This collection brings together the voices of early career researchers (ECRs), whose reflections show how a system in crisis is experienced and navigated at a human scale, while also highlighting the resilience, creativity, and solidarity that point toward pathways forward.